Learning Jawi character game / Nurul Fadhillah Anuar - Anuar, Nurul Fadhillah (2018)
Nowadays, the education processes are not based on the traditional classrooms only but it assisted with interactive learning whereas on the web or mobile application. Therefore learning Jawi character are developed to enhance Jawi learning among primary school kids in their learning because currently teachers are use textbook and flashcards to teach them based on the investigation. However, the Jawi is slowly forgotten because the younger generation to be unfamiliar with the alphabet. Then, they need extra material to help them to recognize and memorize Jawi alphabets in indirect approach. Besides that, the development of the project is based on system development life cycle (SDLC) model. The waterfall model are consist six phase which is the first phase is Knowledge Acquisition, System Requirement, System Design, System Development, Data Analysis and Result Analysis. Knowledge acquisition phase where need to do some research and understand the flow of the project. For the system requirement phase, it will tell about the software and hardware is needed to complete this project. Next is system design, where it will continue to develop the storyboard, design the step by step of the flow and design the user interface. After that, for system development it will use Construct 2. The puzzle method was implemented and the prototype was tested. Then, to collect data analysis a set of questionnaire are distributed on a specific target. After that, a question was collected and the users are given the game as part of the functional testing. After playing the game, they will distribute the same question to test their IQ after playing the game. Result analysis are done when the entire question from the user are analysed and interpreted. Last but not least, for the future enhancement it is recommended to researcher added new features such as 3 dimensional graphics and animations to attract them learn more about Jawi.